Organized crime in Asia - Ward, Richard; Mabrey, Daniel (Henry Stewart Talks, 2008)
Defining organized crime, General characteristics of Asian organized crime, Transnational organized crime, Local crime, The problem of corruption, Cultural and legal factors, Emerging trends, Terrorism and narco-terrorism, Cyber crime and technological crime, New forms of illegal drug activity, Fraud and economic crime, Theft of cultural antiquities, Cross border cooperation, The People's Republic of China, Japan, Korea, Philippines, Cambodia, Vietnam, Myanmar, The future of Asian organized crime, Combating Asian organized crime
Archived at 2022/04/03